We have to solve sqrt (5x-4) + sqrt(11x+4) = 4*sqrt x

sqrt (5x-4) + sqrt(11x+4) = 4*sqrt x

square both the sides

=> (5x - 4) + (11x + 4) + 2*sqrt (5x-4)*sqrt(11x+4) = 16x

=> 16x + 2*sqrt (5x-4)*sqrt(11x+4) = 16x

=> 2*sqrt (5x-4)*sqrt(11x+4) = 0

=> (5x -...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve sqrt (5x-4) + sqrt(11x+4) = 4*sqrt x

sqrt (5x-4) + sqrt(11x+4) = 4*sqrt x

square both the sides

=> (5x - 4) + (11x + 4) + 2*sqrt (5x-4)*sqrt(11x+4) = 16x

=> 16x + 2*sqrt (5x-4)*sqrt(11x+4) = 16x

=> 2*sqrt (5x-4)*sqrt(11x+4) = 0

=> (5x - 4)(11x + 4) = 0

5x - 4 = 0 , gives x = 4/5

11x + 4 = 0, gives x = -4/11. But sqrt (-4/11) is not real.

Therefore the real value of x is **4/5. **